SENYAWA GOLONGAN 2-ARYLBENZOFURAN DAN STILBEN DARI EKSTRAK METILEN KLORIDA (CH2CL2) DAUN Artocarpus fretessi HASSK - Ilyas, Asriani (Teknosains, 2013)
Isolation and identification of secondary metabolites from CH2Cl2 extract of the leaves of Artocarpus fretessi Hassk plant had been performed. Separation techniques used consisted of extraction, fractionation, and purification. The classes of compounds obtained were tested and elucidated based on UV and IR spectroscopy data. Two compounds obtained were 2âarylbenzofuran and stilbene.Keyword : Artocarpus fretessi Hassk, 2âarylbenzofuran, stilbene